2021
DOI: 10.1109/tmi.2021.3069558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning Architectures for Complex Immunofluorescence Nuclear Image Segmentation

Abstract: Separating and labeling each nuclear instance (instance-aware segmentation) is the key challenge in nuclear image segmentation. Deep Convolutional Neural Networks have been demonstrated to solve nuclear image segmentation tasks across different imaging modalities, but a systematic comparison on complex immunofluorescence images has not been performed. Deep learning based segmentation requires annotated datasets for training, but annotated fluorescence nuclear image datasets are rare and of limited size and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 53 publications
(121 reference statements)
0
30
0
Order By: Relevance
“…Cell counting and segmentation is a common challenge in high-throughput analysis of optical microscopy images [8, 9, 12, 33, 34]. Both fully- and weakly-supervised DL approaches were shown to be very powerful to assess these tasks on multiple cell lines [7, 25].…”
Section: Resultsmentioning
confidence: 99%
“…Cell counting and segmentation is a common challenge in high-throughput analysis of optical microscopy images [8, 9, 12, 33, 34]. Both fully- and weakly-supervised DL approaches were shown to be very powerful to assess these tasks on multiple cell lines [7, 25].…”
Section: Resultsmentioning
confidence: 99%
“…This Unet extracts cell boundaries that are processed using 3D watershed along with conditional random fields ( a prediction concept which uses contextual information from previous labels) . (Kromp et al, 2019) and the Mask RCNN architecture was found to outperform the UNet based models in the 2D segmentation task. It may be noted that for evaluation (Zaki et al, 2020) use F1-score, while (Kromp et al, 2019) use under/oversegmentation and aggregated Jaccard index.…”
Section: Acknowledgementmentioning
confidence: 96%
“…Nuclei size often varies signi cantly (from a few microns to tens of microns) among different cell types, cultured cells and tissues. Scale makes a signi cant difference in segmentation accuracy [2,15]. Networks trained on a limited dataset without scale variation or image augmentation, may get locked into recognizing only a limited set of nuclear sizes, resulting in over or under segmentation of instances as well as increased false negatives and splits and merges when applied to a test set containing different nuclear sizes.…”
Section: Effects Of Scalementioning
confidence: 99%
“…Additionally, it suffers from individual user bias and lack of reproducibility. Convolutional neural networks (CNNs) have been adapted for nuclei segmentation in wide-eld uorescence images and bright-eld histology images with great success [1][2][3].…”
Section: Introductionmentioning
confidence: 99%